Planes with solar batteries as a novel tool for Antarctic research: specifics, advantages, possibilities - A. P. Trofimenko (Ukrainian Antarctic Journal, 2012)
The article describes the advantages of unmanned aircraft compared to man-operated planes in scientific research. It is proposed to use solar-powered unmanned aircraft for flights lasting several days without landing at high altitude. There are described technical preconditions required for creation and development of solar-powered aircraft. The planes' specific features and strong sides are reviewed. Based on the author's proposed mathematical model there are calculated dependencies between wing load and speed on the necessary flight altitude. It is shown that a project of solar-powered unmanned aircraft is feasible using current technical developments. There are given characteristics of solar-powered aircraft to be expected in the nearest future.